Terrorism and Communism : a Contribution to the Natural History of Revolution. - Kautsky, Karl (Routledge revivals., 2012)
First published in English in 1920, this work is a reissue of Karl Kautsky's seminal work dealing with the origins and history of the forces at work in revolutionary epochs, which offers pathbreaking insights on the development of civilisation. The opening chapters, dealing with eigthteenth century France, are of special interest to the student of the French revolution. The section devoted to the Commune of Paris offers a stimulating and provocative description of this famous govenment of the working class. The reissue of this controversial and extraordinary work will be welcomed by all those i.